The Role of Parents in the Social-Emotional Development and Independence of Children - Sri Lestari; Diah Wahyuningsih (Manunggal Halim Jaya, 2026)
Alpha generation is a generation that is growing up in the current era. This generation brings very rapid digital transformation. Along with the advancement of new digital technologies, many accompanying problems have also emerged, especially among children. This condition significantly affects children’s emotional development. Children spend more time looking at mobile phone screens than socializing with others. Therefore, there is a need to improve parenting patterns in educating children, as this can influence the development of positive social feelings. This research was conducted at KB ANANDA using a qualitative research method with a phenomenological approach. This approach was applied to understand the phenomenon of children’s emotional development. Fifteen parents who enrolled their children at the institution were selected as the research sample and observed directly. The results of the observations were compared with literature sources as supporting information to strengthen the obtained data. The literature used consisted of books and scientific journals. Based on the discussion of children’s emotional development at school, it can be understood that there are various multidimensional aspects, ranging from internal to external factors. Internal factors include children’s ways of thinking, which influence their personalities. Children under the age of eight tend to have temperamental characteristics that can be categorized as easy or difficult. Children with easy temperaments are generally easier to guide, while children with difficult temperaments are more challenging to direct. External factors include parenting styles, peer interactions, teacher-child relationships, and school regulations. These factors become the main foundation in shaping children’s emotional competence.